So lucky - Griffith, Nicola (Frrar, Straus and Giroux, 2018)
Mara Tagarelli is, professionally, the head of a multimillion-dollar AIDS foundation; personally, she is a committed martial artist. But her life has turned inside out like a sock. She can't rely on family, her body is letting her down, and friends and colleagues are turning away--they treat her like a victim. She needs to break that narrative: build her own community, learn new strengths, and fight. But what do you do when you find out that the story you've been told, the story you've told yourself, is not true? How can you fight if you can't trust your body? Who can you rely on if those around you don't have your best interests at heart, and the systems designed to help do more harm than good? Mara makes a decision and acts, but her actions unleash monsters aimed squarely at the heart of her new community. This is fiction from the front lines, incandescent and urgent, a narrative juggernaut that rips through sentiment to expose the savagery of America's treatment of the disabled and chronically ill. But So Lucky also blazes with hope and a ferocious love of self, of the life that becomes possible when we stop believing lies.